Administrators’ Perception of Teacher-educators’ Exhibition of Pedagogical Skills and Implementation of Early Childhood Education Curriculum in Primary Teachers’ Colleges in Eastern Uganda - Wambi, Moses; Buluma, Alfred; Ludigo, Harriet (East African Journal of Education Studies, 2023)
The major intention of this study was to assess the perception of college administrators on the extent to which Teacher-educators exhibit the required pedagogical Skills to be emulated by their trainees to the expectations of the Ministry of Education and Sports in Uganda. The authors of this paper were motivated by the notion that Teacher-educators ought to exhibit desirable pedagogical Skills as a mentorship strategy to their trainees. There is a persistent public outcry about the pseudo-trained graduates from Primary Teachers’ Colleges (PTCs) in Uganda. The objectives of this study were threefold, namely: (1) identify the pedagogical Skills stipulated in the ECE curriculum for teacher trainees in PTCs; (2) establish the extent to which teacher-educators facilitate their trainees to acquire the required pedagogical Skills in the ECE curriculum; and (3) find out the challenges associated with Teacher-educators’ competencies to exhibit pedagogical Skills in PTCs in Eastern Uganda. A phenomenology research design was adopted with a qualitative approach. Thirty-eight informant interviews and nineteen focus group discussion schedules were conducted with participants who included; Principals, Deputy Principals, the Director of Studies and an ECE Official from Kyambogo University. The key findings indicated that the Primary Teacher Education (PTE) curriculum of 2012 stipulates pedagogical Skills to be exhibited by Teacher-educators to their trainees; however, teacher-educators experienced the inability to exhibit desirable pedagogical Skills for their trainees to emulate. It was difficult for the Teacher-educators to offer what they never possessed. The greatest challenge reported by the majority of the participants was inadequate funding and yet ECE is a practical learning area and limited access to opportunities for Continuous Professional Development (CPD) courses for capacity building was yet another concern. It was therefore, recommended that Teacher-educators be trained to acquire desirable competencies in exhibiting pedagogical Skills so as to mentor and support their trainees. If the quality of teacher education is to be realised as expected, Teacher-educators’ CPDs on pedagogical Skills are crucial. Trainees are expected to tap into the vast experience of their Teacher-educators through mentorship as emphasised by the Vygotsky social-cultural theory.